ART AND CELEBRATION OF FAITH - Elavathingal, Sebastian (Asian Horizons, 2011)
The experience and the expression of faith in the history of the Church have always been seeking embodiment in different cultural forms. Culture is a specifically human good which is at the disposal of the Spirit who proceeds in history manifesting in myriads of forms the marvels of the divine mystery. Culture reveals, realizes and celebrates the Spirit. As all spiritual experiences, the experience of faith has to culminate in celebration. Hence culture has been a concern of the Church in the proclamation of faith from the earliest centuries onwards. In today’s world, as the Church encounters new cultures, an increased awareness of the cultural reality challenges the tasks of faith – proclamation, witness and celebration.